2014
DOI: 10.1155/2014/983103
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Thread Pitch, Helix Angle, and Compactness on Micromotion of Immediately Loaded Implants in Three Types of Bone Quality: A Three-Dimensional Finite Element Analysis

Abstract: This study investigated the influence of thread pitch, helix angle, and compactness on micromotion in immediately loaded implants in bone of varying density (D2, D3, and D4). Five models of the three-dimensional finite element (0.8 mm pitch, 1.6 mm pitch, 2.4 mm pitch, double-threaded, and triple-threaded implants) in three types of bone were created using Pro/E, Hypermesh, and ABAQUS software. The study had three groups: Group 1, different pitches (Pitch Group); Group 2, same compactness but different helix a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
25
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 38 publications
(37 reference statements)
2
25
0
3
Order By: Relevance
“…Studies pertaining to thread pitch and its effect on crestal bone loss level [10], resistance to vertical load [11], and stress distribution [12] have been reported. These studies demonstrated lower thread pitch to have favorable resistance and stress distribution and less crestal bone loss.…”
Section: Discussionmentioning
confidence: 99%
“…Studies pertaining to thread pitch and its effect on crestal bone loss level [10], resistance to vertical load [11], and stress distribution [12] have been reported. These studies demonstrated lower thread pitch to have favorable resistance and stress distribution and less crestal bone loss.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 Implant stability, whether primary or secondary, can be influenced by site related factors such as bone quality and quantity as well as the surgical instrumentation and implant macro-and micro-design features. Several reports have shown improved primary implant stability with implants of specific surface modifications, 12 cutting thread configurations, 13,14 and with implants of tapered designs 15 compared with standard implants. Several reports have shown improved primary implant stability with implants of specific surface modifications, 12 cutting thread configurations, 13,14 and with implants of tapered designs 15 compared with standard implants.…”
mentioning
confidence: 99%
“…10,11 The role of implant macro and microstructures in improving implant stability has been controversial in the evidence-based literature. Several reports have shown improved primary implant stability with implants of specific surface modifications, 12 cutting thread configurations, 13,14 and with implants of tapered designs 15 compared with standard implants. It has also been demonstrated that implants with tapered design and surface modifications can increase implant stability due to the high bone compression generated during insertion 16 and high contact osteogenesis.…”
mentioning
confidence: 99%
“…A estabilidade primária também sofre influência direta da área de contato osso/implante, principalmente devido às características associadas ao design (forma, largura, profundidade, inclinação, face e ângulo da hélice) e ao passo de rosca (ângulo e largura). Baseado nisso, o intertravamento mecânico do modelo rosqueado foi superior ao helicoidal, provavelmente devido ao menor passo de rosca, o qual, além de aumentar a área de superfície, melhora a compactação óssea e, consequentemente, o torque de inserção 26,27 . Já no helicoidal, a macrogeometria com apenas duas roscas de passo longo pode ter gerado menor fricção implante/osso, reduzindo a estabilidade inicial no modelo ósseo avaliado 8,28 .…”
Section: Discussionunclassified